WALLABY Pre-Pilot Survey: the effects of angular momentum and environment on the H i gas and star formation properties of galaxies in the Eridanus supergroup. Issue 2 (11th August 2021) - Murugeshan, C; Kilborn, V A; For, B-Q; Wong, O I; Wang, J; Westmeier, T; Stevens, A R H; Spekkens, K; Kamphuis, P; Staveley-Smith, L; Lee-Waddell, K; Kleiner, D; et al.
ABSTRACT: We use high-resolution ASKAP observations of galaxies in the Eridanus supergroup to study their H i, angular momentum, and star formation properties, as part of the WALLABY pre-pilot survey efforts. The Eridanus supergroup is composed of three sub-groups in the process of merging to form a cluster. The main focus of this study is the Eridanus (or NGC 1395) sub-group. The baryonic specific angular momentum – baryonic mass ( j b − M b ) relation for the Eridanus galaxies is observed to be an unbroken power law of the form $j_{b} \propto M_{b}^{0.57 ± 0.05}$, with a scatter of ∼0.10 ± 0.01 dex, consistent with previous works. We examine the relation between the atomic gas fraction, f atm, and the integrated atomic disc stability parameter q (the f atm − q relation), and find that the Eridanus galaxies deviate significantly from the relation owing to environmental processes such as tidal interactions and ram pressure affecting their H i gas. We find that a majority of the Eridanus galaxies are H i deficient compared to normal star-forming galaxies in the field. We also find that the star formation among the Eridanus galaxies may be suppressed owing to their environment, thus hinting at significant levels of pre-processing within the Eridanus sub-group, even before the galaxies have entered a cluster-like environment.